Tingkat Hen Day Production (HDP) dan Break Event Point (BEP) Usaha Ayam Ras Petelur (Gallus sp) - Hastuti, Dewi; Prabowo, Rossi; Syihabudin, Ahmad Anwar (LPPM Universitas Malikussaleh - Indonesia, 2018)
This study aims to determine the daily egg production level (HDP) and Break Event Point (BEP). The research location and respondents were determined intentionally (purposive sampling) with a total of 4 farmers consisting of 1,000 tail respondents, 1,350 heads, 4,500 heads and 6,000 heads. The data used are primary and secondary data. Data collection techniques are carried out by interviewing, recording and observing. The analysis model used is a descriptive analysis model with verbal and mathematical methods. The verbal method is a way of using words to explain a thing, while a mathematical method uses break event point (BEP) analysis. Based on the results of the study it was found that the production level of 51-day Hen Day production (HDP) of laying hens aged 85 weeks between 85.1% -85.3% . Break Event Point (BEP) production obtained from a scale of 1,000 head was 30,379.5 kg, 1,350 tails of 36,282.5 kg, 4,500 tails of 124,180 kg, and 6,000 tails of 159,231.5 kg. Break Event Point (BEP) prices on a 1,000-tail scale of Rp. 16,893, 1,350 scale of Rp. 14,965, a 4,500 scale of Rp. 15,349 and the scale of 6,000 is Rp. 14,698. The conclusion of this study is that the HDP level is still below standard because the maintenance system for laying hens has not been maximized while the yield of the product and the rupiah is above the BEP value so that the laying hens business produces profits